EKSTRAKSI HIJAU SENYAWA BIOAKTIF DARI ALGA MERAH (Eucheuma cottoni) MENGGUNAKAN PELARUT EUTEKTIK DAN APLIKASINYA DALAM SEDIAAN LOSION - Rahmalia, Winda; Adhitiyawarman, Adhitiyawarman; Sayekti, Endah; Prayitno, Dwi Imam (Indonesian Journal of Pure and Applied Chemistry, 2026)
The need for environmentally responsible extraction techniques has driven the development of green alternatives to conventional organic solvents. Deep eutectic solvents (DESs) offer a sustainable option due to their low toxicity, biodegradability, and simple preparation. In this study, a DES composed of glycine, glycerol, and water (1:11:15 molar ratio) was used as a green extraction medium to isolate bioactive compounds from the red algae (Eucheuma cottonii), providing an eco-friendly solution for efficient marine bioresource utilization. This final product offers a simplified process, as the resulting extract requires no further separation prior to application. The DES exhibited favourable physicochemical properties, including a pH of 5, density of 1300.14 kg/m³, viscosity of 0.0198 Pa·s, and a freezing point below 263.15 K. Phytochemical screening of the DES-based extract confirmed the presence of phenolic and terpenoid compounds. The extract was directly incorporated into sunscreen lotion formulations at concentrations ranging from 0 to 15% (w/w). All formulations showed good homogeneity, with the highest sun protection factor (SPF) value of 8.37 observed in the lotion containing 15% red algae extract. This research shows the success of extracting natural anti-UV ingredients in an environmentally friendly and efficient manner.